Biodeterioration of Antarctic fossil penguin bones caused by lichens from the Eocene La Meseta Formation - García, Renato Andrés; Acosta Hospitaleche, Carolina Ileana Alicia; Marquez, Gonzalo Javier (Polar Biology)
A large part of the Antarctic surface is covered by lichens since they can withstand extreme environmental conditions. Lichens are primary colonizers and contribute to soil formation by deteriorating rocks through a combination of chemical and physical mechanisms. Therefore, fossil remains found exposed on the surface are usually colonized by epilithic and endolithic lichens. The objective of this work is to determine the biodeterioration generated by lichens on fossil remains and its taphonomic implications. We identified the presence of the euendolithic lichens Lecidea andersonii and Athallia holocarpa growing into fossil penguin bones from Antarctica. The bioerosive damage was evaluated using light and electron microscopic techniques. Pits corresponding to apothecium and sinuous thin fissures remodeled, or in some cases produced, by hyphae were distinguished from the cracks originating from physical weathering. The maximum depth that hyphae extend inside the bone, probably constrained by the light supply, was established to be 2.5 mm. We provided a tool for the reconstruction of the chronology of the taphonomic events, describing the type and magnitude of the damage into the bones. Fil: García, Renato Andrés. Universidad Nacional de Avellaneda; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Marquez, Gonzalo Javier. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Cátedra de Palinología; Argentina